Impact of platform design on cross-language information exchange - Hale, SA (Association for Computing Machinery, 2012)
This paper describes two case studies examining the impact of platform design on cross-language communications. The sharing of off-site hyperlinks between language editions of Wikipedia and between users on Twitter with different languages in their user descriptions are analyzed and compared in the context of the 2011 Tohoku earthquake and tsunami in Japan. The paper finds that a greater number of links are shared across languages on Twitter, while a higher percentage of links are shared between Wikipedia articles. The higher percentage of links being shared on Wikipedia is attributed to the persistence of links and the ability for users to link articles on the same topic together across languages.